Corifollitropin alfa: a new recombinant FSH gonadotropin analog. (July 2011) - Prados, Nicoláás; Pellicer, Antonio; Fernandez-Sanchez, Manuel
Corifollitropin alfa (also referred to originally as follicle-stimulating hormone [FSH]––carboxi terminal peptide and Org-36286) is a new artificial gonadotropin commercially available for women undergoing controlled ovarian follicle stimulation for IVF or intracytoplasmic sperm injection procedures. It is an artificial chimeric recombinant FSH analog, and its development has taken more than 20 years in order to show its functionality, safety and efficacy. Corifollitropin alfa has a similar functionality to natural FSH but with a longer half-life, among different pharmacokinetic parameters. This has allowed for the development of a new protocol with gonadotropin-releasing hormone antagonists, where the first seven daily injections of 150 IU recombinant have been substituted by a single initial 100 or 150 µµg Corifollitropin alfa dose with no safety or efficacy differences, measured by either the number of retrieved oocytes or pregnancy rates.